2017
DOI: 10.1007/s00223-017-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Lift with Beta-Tricalcium Phosphate (β-TCP) in Edentulous Patients: A Nanotomographic and Raman Study

Abstract: Sinus lift elevation restores bone mass at the maxilla in edentulate patients before the placement of dental implants. It consists of opening the lateral side of the sinus and grafting beta-tricalcium phosphate granules (β-TCP) under the olfactory membrane. Bone biopsies were obtained in five patients after 60 weeks. They were embedded undecalcified in poly(methyl methacrylate) (pMMA); blocks were analyzed by nanocomputed tomography (nanoCT); specific areas were studied by Raman microspectroscopy. Remnants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…It has been recently reported that both osteoclasts and activated macrophages resorb β‐TCP, and these macrophages are positive for TRAP staining (Chappard et al, ; Pascaretti‐Grizon et al, ). It has been also reported that macrophages play a key role in β‐TCP induced osteogenesis and favor osteoblastogenesis from stromal cells present in the bone marrow (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently reported that both osteoclasts and activated macrophages resorb β‐TCP, and these macrophages are positive for TRAP staining (Chappard et al, ; Pascaretti‐Grizon et al, ). It has been also reported that macrophages play a key role in β‐TCP induced osteogenesis and favor osteoblastogenesis from stromal cells present in the bone marrow (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chappard et al recently shown that both osteoclasts and activated macrophages act together to resorb β‐TCP. It has been shown that these macrophages are also positive for the TRAP reaction (Chappard et al, ; Pascaretti‐Grizon et al, ). Furthermore, there are many studies that bisphosphonates are effective in macrophage depletion (Rogers et al, ; Sabatino et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[26,38] Raman spectroscopy and imaging also allow evaluation of the hydration of the different area of the graft as MMA infiltrates microporosity and substitutes to water in hydrated tissues during histological embedding. [17,29,46] The most typical peaks is at 813 cm −1 (C O C) and does not overlap with peaks of bone or β-TCP. Hydration, defined at the ratio of 813 cm −1 /ν1 phosphate band, reflects the original water content of the tissue as, in spectroscopy, the ratio of two peak intensities is proportional to the relative amounts of the two corresponding species.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by a number of papers in the literature, β-TCP is resorbed in vivo by macrophages and osteoclasts that engulf elementary grains of the biomaterial in their cytoplasm. [24,29,47,48] Although these cells can be identified by nanocomputed tomography by their β-TCP content, [[29]] the resolution of our Raman images are not sufficient to identify them clearly. However, some signals are observed in the marrow spaces and do not correspond to a background noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation